Human inborn errors of immunity associated with IRF4 - Thouenon, Romane; Kracker, Sven (Frontiers in Immunology, 2023)
The transcription factor interferon regulatory factor 4 (IRF4) belongs to the IRF family and has several important functions for the adaptive immune response. Mutations affecting IRF family members IRF1, IRF3, IRF7, IRF8 or IRF9 have been described in patients presenting with inborn errors of immunity (IEI) highlighting the importance of these factors for the cellular host defense against mycobacterial and/or viral infections. IRF4 deficiency and haploinsufficiency have been associated with IEI. More recently, two novel IRF4 disease causing mechanisms have been described due to the characterization of IEI patients presenting with cellular a supprimé: associated to immunodeficiency associated with agammaglobulinemia. Here we review the phenotypes and physiopathological mechanisms underlying IEI of IRF family members and in more depth of IRF4.